Ensuring Engagement in English Language Learning Activities: Teachers’ Practices in Sunwal Municipality. - Bashyal, Hari Prasad (Devkota Journal of Interdisciplinary Studies, 2025)
This study investigates the practices employed by English language teachers in Sunwal Municipality to ensure student engagement in English language learning activities. As language acquisition is significantly influenced by student engagement, the research focuses on identifying the strategies, methodologies, and classroom practices that promote active participation among learners. Through qualitative methods, including interviews and classroom observations, the study explores how teachers adapt their teaching techniques to enhance students’ motivation, interest, and overall involvement in language learning activities. The findings highlight the importance of varied instructional approaches, interactive activities, and a supportive learning environment in fostering engagement. The study also addresses the challenges teachers face in maintaining consistent student involvement and offers insights into potential solutions to improve teaching practices in the context of Sunwal Municipality. The results contribute to the broader understanding of effective language teaching strategies and provide valuable recommendations for educators to enhance student engagement in English language classrooms.